Relationship Between Community Knowledge and Flood Preparedness in Environment V, Dwikora Village - Yonlafado Simanjuntak, Edriyani; Parida Sipayung, Normi; Hutajulu, Johansen; Fahrozi, Wawan (Universitas Kusuma Husada Surakarta, 2025)
Floods have an impact on the community, so that it is important for them to have knowledge in dealing with floods in order to reduce the risk and be responsive to flood conditions that will occur. The purpose of this study was to identify the Relationship between Knowledge and Flood Preparedness in Environment V, Dwikora Village. This research method is descriptive correlation with an approach using a Cross Sectional design. The population is the community of Environment V Dwikora Village with a sample size of 229 respondents using Purposive sampling techniques. The research instrument used a questionnaire and used the chi-square test. The results of the study showed that the knowledge of the community in Environment V, Dwikora Village, was mostly knowledgeable, as many as 95 people (41.5%) and had flood preparedness in the category of not prepared as many as 116 people (50.7%). Statistical tests showed that there was a relationship between community knowledge and flood preparedness with a p value = 0.000 (<0.05). It is recommended that efforts be made to increase community knowledge about flood preparedness through education and training programs, as well as providing accurate information about flood preparedness.